When do disarmament, demobilisation and reintegration programmes succeed? - Lilli Banholzer (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
One of the problems in post-war societies is finding ways of convincing former combatants to hand in their weapons and reintegrate into civil society. In an attempt to facilitate the transition from war to peace, DDR (disarmament, demobilisation and reintegration) programmes have become key components of national and international efforts to pacify post-conflict societies. Assisting fighters to gain a foothold in civil society is thought to prevent them from returning to combat and hence to avoid a resumption of hostilities in the long run. In line with sustained investments in DDR programmes, as well as with a noteworthy increase in the number and scope of such programmes, a growing – albeit relatively small – body of literature is attempting to catch up with these developments. In an effort to gather what we know about the factors that contribute to the success of DDR programmes, this discussion paper provides a synthesis of the current literature. While emphasising the emerging body of quantitative research, it also draws on reports by practitioners and in-depth case studies in response to two critical questions: How effective are DDR programmes? What factors and circumstances contribute to or impede their success? Analytically, this paper thereby locates findings in the literature at three levels: the macro level, i.e. context-specific factors; the meso level, i.e. programme factors; the micro level, i.e. individual factors.
Keywords: 330; Sicherheit; Frieden und fragile Staaten; Wirksamkeit und Evaluierung